2008
DOI: 10.1039/b808225a
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid sensor for M. tuberculosis detection based on surface plasmon resonance

Abstract: Cysteine modified NH 2 -end peptide nucleic acid (PNA) (24-mer) probe and 5¢-thiol end labeled deoxyribonucleic acid (DNA) probes specific to Mycobacterium tuberculosis have been immobilized onto BK-7 gold coated glass plates for the detection of complementary, one-base mismatch, non-complementary targets and complementary target sequence in genomic DNA of Mycobacterium tuberculosis using a surface plasmon resonance (SPR) technique. The DNA/Au and PNA/Au bio-electrodes have been characterized using contact ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…It has been found that upon decreasing the concentration of the complementary target significant change in reflectance angle (m o ) observed from 40 to 2 fM. Figure 6 shows improved detection limit (∼500 times) compared to literature ( Table 2) [39][40][41][42][43][44]. Kinetic calculations have been carried out for complementary target having association constant and dissociation constant as k a (m −1 s −1 )=6.68×10 4 ±2.3 and k d (s −1 )= 5.6×10 −3 ±0.01, respectively.…”
Section: Hybridisation Studies Using Surface Plasmon Resonancementioning
confidence: 88%
“…It has been found that upon decreasing the concentration of the complementary target significant change in reflectance angle (m o ) observed from 40 to 2 fM. Figure 6 shows improved detection limit (∼500 times) compared to literature ( Table 2) [39][40][41][42][43][44]. Kinetic calculations have been carried out for complementary target having association constant and dissociation constant as k a (m −1 s −1 )=6.68×10 4 ±2.3 and k d (s −1 )= 5.6×10 −3 ±0.01, respectively.…”
Section: Hybridisation Studies Using Surface Plasmon Resonancementioning
confidence: 88%
“…Kinetic data have been reported for some SPR-based applications, and DNA and PNA probes have been compared from an analytical perspective. For instance, Prabhakar et al [72] quantified the values of the association and dissociation rate constants (K a and K d ) for the DNA complementary sequence for PNA/Au (8.5× 10 4 m −1 s −1 and 3.6×10 −3 s −1 , respectively) and DNA/Au (2.5×10 4 m −1 s −1 and 1.1×10 −3 s −1 ) bioelectrode, thus demonstrating that the results were threefold better when PNA probes were used. Furthermore, no binding with the singlebase mismatched DNA target was observed for the PNAAu bioelectrode.…”
Section: Optoelectronicmentioning
confidence: 99%
“…We have also explored to develop clinical diagnostic sensors using surface plasmon resonance (SPR) [12][13][14][15]. These techniques are unique in terms of the target molecule, specificity, and signal-producing procedure, and they are all based on a common highly sensitive optical biosensing platform with a label-free sensing and shared signal amplification mechanism.…”
Section: Introductionmentioning
confidence: 99%